SPE Russian Oil and Gas Conference and Exhibition 2010
DOI: 10.2118/136335-ru
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Impact of an Intelligent Well Completion on the Oil Production Uncertainty (Russian)

Abstract: Анализ влияния скважин с интелликтуальной компоновкой на уровень неопределенности нефтедобычи И.М. Гребенкин и Д.Р.Дэвис, Университет Хериот-Ватт Авторское право 2010 г., Общество инженеров-нефтяников Настоящий документ был подготовлен для презентации на Российской технической нефтегазовой конференции и выставке SPE 2010 в Москве, Россия, 26-28 октября 2010 г.Настоящий документ был выбран для презентации программным комитетом SPE по итогам анализа информации, содержащейся в реферате, предоставленном автором (а… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Nevertheless, economic analysis shows that latter development option for this subsea field in 100 m water depth located in a mature area had a greater NPV, mainly due to the reduced capital investment required. Moreover, as shown previously by (Grebenkin and Davies 2010), the operational flexibility of the intelligent completion can reduce the impact of unexpected events (e.g. fast water breakthrough) and reduce production uncertainty.…”
Section: Commercial Network Optimisation Software "Critical-water-cutmentioning
confidence: 66%
See 1 more Smart Citation
“…Nevertheless, economic analysis shows that latter development option for this subsea field in 100 m water depth located in a mature area had a greater NPV, mainly due to the reduced capital investment required. Moreover, as shown previously by (Grebenkin and Davies 2010), the operational flexibility of the intelligent completion can reduce the impact of unexpected events (e.g. fast water breakthrough) and reduce production uncertainty.…”
Section: Commercial Network Optimisation Software "Critical-water-cutmentioning
confidence: 66%
“…Passive Inflow Control Devices allow equalization of the production from different zones, reduce horizontal well's "heel-toe" effect and, as a result, increase the sweep efficiency (Birchenko et al 2009). By contrast, "active" devices -Inflow Control Valves (ICVs) -are controlled from the surface in order to reduce undesired fluid production, improve the recovery factor, avoid costly well interventions and reduce production uncertainty (Grebenkin and Davies, 2010). However, many oil companies today still do not feel confident in investing in the latter, more expensive, technology.…”
Section: Introductionmentioning
confidence: 99%
“…They differ in the porosity and permeability distributions. The correlation length values and anisotropy in the orientation of each layer were randomly generated based on the parameters listed in Table 1 same as (Grebenkin and Davies, 2010).…”
Section: Variations Of Uncertain Geological Parametersmentioning
confidence: 99%
“…Manceau et al (Manceau et al, 2002) and Grebenkin (Grebenkin and Davies, 2010) suggested using an experimental design technique coupled with a response surface methodology (RSM) to quantify the impact of reservoir uncertainties on production forecasts. Although, the method reduces the time required for the analysis, the development of an appropriate RSM for cases with high degrees of complexity and uncertainty is not always an easy task.…”
Section: Variation Of the Dynamic Uncertaintiesmentioning
confidence: 99%
“…It has previously been shown by (Birchenko, Demyanov et al 2008;Grebenkin and Davies 2010) to be a suitable candidate for IW. It has previously been shown by (Birchenko, Demyanov et al 2008;Grebenkin and Davies 2010) to be a suitable candidate for IW.…”
Section: Iw Monitoring System Design Examplementioning
confidence: 99%